Doped Lead Halide White Phosphors for Very High Efficiency and Ultra‐High Color Rendering. (16th January 2020) - Yuan, Hailong; Massuyeau, Florian; Gautier, Nicolas; Kama, Antoine Blaise; Faulques, Eric; Chen, Fei; Shen, Qiang; Zhang, Lianmeng; Paris, Michael; Gautier, Romain
Abstract: Near‐UV‐pumped white‐light‐emitting diodes with ultra‐high color rendering and decreased blue‐light emission is highly desirable. However, discovering a single‐phase white light emitter with such characteristics remains challenging. Herein, we demonstrate that Mn doping as low as 0.027 % in the hybrid post‐perovskite type (TDMP)PbBr4 (TDMP= trans ‐2, 5‐dimethylpiperaziniium) enables to achieve a bright pure white emission replicating the spectrum of the sun's rays. Thus, a white phosphor exhibiting an emission with CIE coordinates (0.330, 0.365), a high photoluminescence quantum yield of 60 % (new record for white light emission of hybrid lead halides), and an ultra‐high color rendering index (CRI=96, R9=91.8), corresponding to the record value for a single phase emitter was obtained. The investigation of the photoluminescence properties revealed how free excitons, self‐trapped excitons, and low amount of Mn dopants are coupled to give rise to such pure white emission. Abstract : Weißer als Weiß : Das Dotieren von (TDMP)PbBr4 mit geringsten Mengen an Mn 2+ ergibt einen Leuchtstoff mit heller, reiner, weißer Emission mit sehr hoher Effizienz (PLQY=60 %) und ultrahohem Farbwiedergabeindex (CRI=96). TDMP= trans ‐2, 5‐Dimethylpiperazinium.